AB0321 IL-6 Blockade Reduces Circulating N-Terminal Pro-Brain Natriuretic Peptide Levels in Patients with Active Rheumatoid Arthritis. (10th June 2014) - Inomata, H.; Kobayashi, H.; Kobayashi, Y.; Ikumi, N.; Yokoe, I.; Nagasawa, Y.; Sugiyama, K.; Nozaki, T.; Shiraiwa, H.; Kitamura, N.; Iwata, M.; Takei, M.
Abstract : Background: Patients with rheumatoid arthritis (RA) have a 1.5–2.0 fold higher risk of developing congestive heart failure than the general population. Small increases in N-terminal pro-brain natriuretic peptide (NT-proBNP) levels predict left ventricular (LV) dysfunction, and the LV myocardium is the primary site of NT-proBNP production. Data relating to the effects of interleukin (IL)-6 blocking agents on circulating NT-proBNP levels in patients with active RA are lacking but may be informative. To our knowledge, there are no published reports regarding the effect of tocilizumab (TCZ) treatment on NT-proBNP levels. Objectives: To test the hypothesis anti-IL-6 therapy might reduce circulating NT-proBNP levels. Methods: RA patients with active disease without a clinical diagnosis of cardiovascular disease (CVD) and with an inadequate clinical response to DMARDs were enrolled. The patients received TCZ once a month after 24 weeks. Serum NT-pro BNP levels were measured on the Cobas 6000 modular analyzer simultaneously on stored baseline and 24-week samples, and NT-pro-BNP levels ≥100 pg/mL were considered elevated. We explored the associations between NT-pro BNP and the RA disease activity score for 28 joints: erythrocyte sedimentation rate (DAS28-ESR) and Simple Disease Activity Index (SDAI) scores. The anti-citrullinated protein antibody (ACPA) titre was divided into high and low levels using a cut-off of 30 units/mL. Correlations between the biomarkers and changes in circulating NT-proBNP levels were evaluated using the Spearman rank test, and multivariable linear regression analyses of the correlates were performed. Results: Sixty RA patients (mean age, 60.4±10.4 years; 75% female) were enrolled. The DAS28-ESR and SDAI at baseline were 4.57±1.35 and 22.5±12.7, respectively. The 24-week DAS28-ESR and SDAI scores were significantly lower than those at baseline (p=0.04, p=0.03, respectively). The NT-proBNP levels at baseline were approximately 31% higher than normal levels, and the median (interquartile range) levels significantly decreased from baseline (131.78 [52.81–230.24] pg/mL) to 24 weeks (57.13 [29.50–128.67] pg/mL, p=0.004) following TCZ treatment. The change in NT-proBNP levels was significantly correlated with the change in the SDAI score and swollen joints count (SJC) ( r =0.455, p=0.003, r =0.395, p=0.004, respectively). The baseline NT-proBNP levels in the high ACPA group tended to be higher than in the low ACPA group (p=0.07). After adjustment for age, gender, ESR, and RA duration, the association between the change in NT-proBNP levels and the change in SJC remained significant (p=0.023). Conclusions: The NT-proBNP level was higher than normal in patients with active RA without CVD; this may indicate subclinical left ventricular dysfunction. Furthermore, our results indicate the NT-proBNP levels decreased by approximately 38% with TCZ treatment, which was related to a reduction in disease activity. Therefore, TCZ treatment may directly influence the anti-inflammatory effect of IL-6 on the myocardium. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2189